An Exploration of the Department of Health’s Human Papillomavirus Policy to Vaccinate Girls aged 12-18 years with the Cervarix Vaccine: A Critical Review. - Campbell, Harriet (2011)
This critical review explores the debates that surround the English NHS funded human papillomavirus policy. At present girls aged 12-18 years are being vaccinated with the bivalent vaccine (Cervarix). It aims to reduce the incidence of cervical cancer due to the connection between HR HPV and cancer development. The critical review method was justified because it enabled a large amount of literature to be critically analysed.